Zinc Tetracyanoplatinate: A Reversible Luminescence‐Based Ammonia Sensor. Issue 38 (22nd May 2019) - Varju, Bryton R.; Wollschlaeger, Sara A.; Leznoff, Daniel B.
Abstract: ZnPt(CN)4 was shown to be an effective material for ammonia sensing, and can be synthesized using either solution or mechanochemical methods. A combination of luminescence and Raman spectroscopy revealed that multiple species are involved in the reaction between ammonia and ZnPt(CN)4 . The crystal structure of one of these species, Zn(NH3 )2 Zn(NH3 )3 (Pt(CN)4 )2, was elucidated. Detection of ammonia vapor down to 50 ppm in air was accomplished by monitoring the luminescence spectrum. The reaction between ZnPt(CN)4 and ammonia vapor is reversible, and can be cycled multiple times by either flowing air over the material or heating. ZnPt(CN)4 also has a relatively high thermal stability, decomposing only when heated above 420 °C. Abstract : Perfect sense : The coordination polymer ZnPt(CN)4 reversibly detects ammonia vapor through changes in emission down to 50 ppm and also by ν CN changes in the Raman spectrum.